Fabrication of Polyaniline–Carbonnanofibers for Hydrochloric Acid and Ammonia Sensing at Room Temperature - Thamir A. A. Hassan; Izzat M. Al-Essa; Ekram A.Al-Ajaj; Abdul Kareem M. Ali (Engineering and Technology Journal, 2014)
The multiwall Carbon nanotubes(CNTs) of 0.25wt %,0.5wt % and 1wt% was added to 0.1 M distilled aniline under reflex procedure with 0.3 H2SO4 for fabricating PANI/CNTs nanofibers. A cyclic potential ranged from -100 mV to 1500 mV was applied with six repetition on working electrodes stainless steel (SUS 304) which were dipped in these solutions at scan rate of 30mV s-1 at room temperature. Scanning Electron Microscope (SEM) images showed that the PANI-CNTs nanofibers structure with diameters range (50nm-70 nm). In the liquid type sensing, it was found that with the increase of HCl concentrations, the value of current density (J) could be raised and found pronounced at 3000 ppm and 4000ppm concentration along with PANI/0.5 wt %CNTs and PANI/1 wt% CNTs sensors out of the four corresponding four solutions and for sensors. The reason behind that may be the enhancement of more efficient transfer of charges. On the other hand a reduction in current density (J) was obtained with increasing concentration of NH3 and clearly observed at 1000 ppm and 2000 ppm for PANI/0.5 wt %CNTs and PANI/1 wt% CNTs sensors.